Theoretical Isomerization Study of [(R)CalixTMS 2]Ge Macrocycles - ARMAN TAHERPOUR, AVAT; YOUSEFIRAD, MOSTAFA (Asian Journal of Chemistry, 2010)
Design, synthesis and study about the behaviours of liquid crystals and gauge theory for these compounds are two main concepts of this family of compounds. The calix[n]arenas are a class of chalice-like macrocyclic molecules that have recently attracted widespread attention as complex molecules with liquid crystal behaviours. The calix[n]arenas have been frequently used as ancilliary ligands for studying the chemistry of transition and main group metals. The 1,3-bis(trimethyl silyl)ether of p-tert-butyl calix[4]arene, [(t-Bu)calixTMS2]H2, has been synthesized and used as a dianionic ligand for Ge. The complex of [(t-Bu)calixTMS2]Ge exhibits exo/endo isomerism. The structural properties of [(Rp)calixTMS2]Ge, (Rpara =H, CH3, t-Bu) and the inter conversion of exo ↔endo isomers were investigated by the use of PM3 data.